PENGARUH PEMAHAMAN WAJIB PAJAK, KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA SURAKARTA - Musa Zul Hazmi; Suhendro Suhendro; Riana Rahcmawati Dewi (Universitas Jember, 2020)
This research was conducted to assess whether understanding taxpayers, service quality, and tax penalties against the KPP Pratama Surakarta. Population in this research are Individual Taxpayers at KPP Pratama Surakarta. Data sources in this study are primary data collected by researchers through questionnaires distributed to 110 respondents, but returned and complete questionnaires were 60 respondents . This research is a quantitative research with 60 respondents at KPP Pratama Surakarta. The data selection method is the random sampling method. The data in this study were processed using the SPSS 21.0 for Windows application. Based on research results understanding taxpayers, service quality, and tax sanctions have a significant effect on taxpayer approval. Understanding tax regulations becomes a benchmark for taxpayers in completing their tax obligations. The quality of service provided by the tax authorities influences taxpayer compliance, indicating that service quality is a benchmark to make taxpayers obey. The existence of tax sanctions that are given expressly will increase the level of compliance, because making taxpayers afraid of being subjected to these sanctions and the stipulation of tax sanctions will deter taxpayers and clear and firm sanctions. Keywords: Understanding, Service Quality, Penalties, Taxpayers